Pengaruh Pendekatan Multirepresentasi Terhadap Hasil Belajar Fisika Dasar Mahasiswa Pada Materi Hukum 1 Termodinamika. - Tulandi, Djeli Alvi; Rondonuwu, Anneke Tienneke; Komea, Aron Rixcy (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
This research was conducted related to the use of multi-representation approach learning of physics. The purpose of this study to determine the effect of the multi-representation approach to student physics learning outcomes in learning. The type of representations used in this study are verbal representations, mathematical representations and graph representations. This type of research in this study is quasi-experimental or quasi-experimental research using the One Group Pretest-Posttest Design research design. This research was conducted at the Department of Physics at Manado State University in the first semester students of physics education courses totaling 20 students. Data collection techniques use essay tests to determine learning outcomes. From the research results obtained an average value before treatment was 17.8 while after treatment was 80.45. Hypothesis testing that has been done states that Ha is accepted, it is proven by the results of the study showing the price of tcount 2.13> ttable 2.086. Therefore learning by using a multi-representation approach has an effect in improving student learning outcomes.